Effect of bismuth doping on zircon-type gadolinium vanadate: Effective electrocatalyst for determination of hazardous herbicide mesotrione. (February 2023) - Karuppaiah, Balamurugan; Jeyaraman, Anupriya; Chen, Shen-Ming; Chavan, Prajakta R.; Karthik, Raj; Hasan, Mahmudul; Shim, Jae-Jin
Abstract: Pesticides are used to promote the growth of plants and crops by killing weeds and other pests. On the other hand, overused and unused pesticides can leach into groundwater and agricultural lands, easily contaminating water, air, and soil resources. Doping with metal ions is an effective method to improve the catalytic activity of potential electrode materials. In the present study, an electrochemical sensor based on Bi 3+ -doped gadolinium vanadate nanoparticles (GVB NPs) was fabricated for sensitive and selective detection of harmful pesticide mesotrione (MST). The crystalline nature, functional groups, and elemental composition of the prepared electrocatalysts were confirmed by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy. Field-emission scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HR-TEM) showed that the undoped gadolinium vanadate had a rice-like nanostructure and was designated as GV NRs, while GVB had the morphology of nanoparticles. The fabricated electrode exhibited a well-resolved MST reduction peak in cyclic voltammetry and linear sweep voltammetry (LSV). Bismuth doping effectively enhanced the MST reduction and produced a stronger cathodic current response than bare and GV NRs-modified GCE. Moreover, GVB NPs/GCE show a nanomolar detection limit of 45 nM with a sensitivity of 0.43 μA μM −1 cm −2 . The proposed sensor showed good repeatability, reproducibility, and stability in LSV analysis. The fabricated MST sensor was successfully applied to the analysis of real samples (river water and corn) with good recovery results. Graphical abstract: Image 1 Highlights: Bismuth doped gadolinium vanadate (GVB NPs) nanoparticles were prepared. A new electrochemical sensor was reported based on GVB NPs for herbicide Mesotrione detection. The GVB NPs exhibits good electrocatalytic activity towards Mesotrione detection. Constructed electrode owns a LOD (45 nM) and higher sensitivity (0.45 μA μM −1 cm −2 ). The good recovery results were obtained for mesotrione determination in real sample analysis.